Clinical efficacy and neuroprotective effects of brimonidine in the management of glaucoma and ocular hypertension - Anna Galanopoulos (Dove Medical Press, 2008)
Anna Galanopoulos1, Ivan Goldberg21Senior Visiting Ophthalmologist, South Australian Institute of Ophthalmology and Dept of Ophthalmology and Visual Sciences, University of Adelaide, South Australia; 2Clinical Associate Professor, University of Sydney, Australia; Head, Glaucoma Unit, Sydney Eye Hospital, Sydney, Australia, Director, Eye Associates, Sydney, AustraliaAbstract: Elevated intraocular pressure (IOP) is a significant risk factor for the development and progression of glaucomatous optic neuropathy, but increasingly we appreciate that non-pressure dependent factors, are key to our understanding of the pathophysiology of these neurodegenerative diseases, that target the retinal ganglion cell. As we try to expand therapy beyond IOP control, medications are being assessed for their neuroprotective abilities. Brimonidine is an effective ocular hypotensive treatment both as a first and second line agent, in the management of glaucoma and ocular hypertension. Brimonidine tartrate 0.2% is generally safe and well tolerated, with its safety profile further enhanced in the altered formulation brimonidine-Purite™ 0.1%. Beyond brimonidine’s pressure lowering capacity, laboratory and early clinical evidence supports its neuroprotective potential. We await validation of this in human clinical trials.Keywords: brimonidine, neuroprotection, clinical effectiveness, tolerability